AVALIAÇÃO DA DIETA DE PIMELODUS BRITSKII GARAVELLO & SHIBATTA, 2007 EM UMA ÁREA AQUÍCOLA DO RESERVATÓRIO DE SALTO CAXIAS, PARANÁ, BRASIL - SANTOS, Joice Neila; SANTOS, Adriani Cristina Monteiro; KASHIWAQUI, Elaine Antoniassi Luiz (ANAIS DO ENIC, 2020)
-